2015
DOI: 10.1371/journal.pone.0118586
|View full text |Cite
|
Sign up to set email alerts
|

Both Food Restriction and High-Fat Diet during Gestation Induce Low Birth Weight and Altered Physical Activity in Adult Rat Offspring: The “Similarities in the Inequalities” Model

Abstract: We have previously described a theoretical model in humans, called “Similarities in the Inequalities”, in which extremely unequal social backgrounds coexist in a complex scenario promoting similar health outcomes in adulthood. Based on the potential applicability of and to further explore the “similarities in the inequalities” phenomenon, this study used a rat model to investigate the effect of different nutritional backgrounds during gestation on the willingness of offspring to engage in physical activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 69 publications
5
34
1
Order By: Relevance
“…In our study, the sex differences in the chow consumption of IUGR rats during the habituation period could be related to variations in the interpretation of new environmental cues or to a differential response to the stress of the new apparatus in males vs. females, resulting in higher chow consumption in IUGR males and lower consumption in IUGR females during this period. Interestingly, other studies from our research group had also found that FR/ Adlib males and females behave in opposite ways when placed in an environment containing a running wheel, with IUGR males showing decreased spontaneous physical activity and IUGR females showing increased activity as compared to controls (Cunha Fda et al, 2015). Thus, it appears that IUGR males and females exhibit a peculiar pattern of energy intake/expenditure when facing a novel environment.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In our study, the sex differences in the chow consumption of IUGR rats during the habituation period could be related to variations in the interpretation of new environmental cues or to a differential response to the stress of the new apparatus in males vs. females, resulting in higher chow consumption in IUGR males and lower consumption in IUGR females during this period. Interestingly, other studies from our research group had also found that FR/ Adlib males and females behave in opposite ways when placed in an environment containing a running wheel, with IUGR males showing decreased spontaneous physical activity and IUGR females showing increased activity as compared to controls (Cunha Fda et al, 2015). Thus, it appears that IUGR males and females exhibit a peculiar pattern of energy intake/expenditure when facing a novel environment.…”
Section: Discussionmentioning
confidence: 48%
“…Gestation was confirmed at day 1 by sperm-positive vaginal smears. On gestation day 10, dams were randomly allocated to a control group (Adlib), which received an ad libitum diet of standard laboratory chow (NUVILAB s ) or a 50% food restriction group (FR), which was given 50% of the intake of the ad libitum-fed dams (determined by the quantification of normal intake in a cohort of pregnant Sprague Dawley rats) (Cunha Fda et al, 2015;Desai et al, 2005). These diets were provided from gestation day 10 through to the 21st day of lactation.…”
Section: Methodsmentioning
confidence: 99%
“…Offspring of dams receiving a high-fat diet may have higher corticosterone levels as adults [14]. Maternal high-fat diets may also lead to increased adult leptin [9,15,16] and decreased adiponectin [15].…”
Section: Introductionmentioning
confidence: 99%
“…preference for wheel running versus lever pressing for food [14]. Inequalities in nutrition -food restriction and/ or high-fat diet during gestation induced reduced birth weight, and altered also the level of PA in adult offspring [11].…”
Section: Interrelationships Between Early Nutrition Related To Physicmentioning
confidence: 98%
“…The effect of PA is closely interrelated with the impact of nutrition manifesting energy balance and turnover, and the effects of these relationships can be mediated and reflected also as delayed effects later in life. Changed nutrition of both, restricted and high fat diet during gestation can alter, along with low birth weight also physical activity [11].…”
Section: Introductionmentioning
confidence: 99%